ANALISIS RESPON BATIMETRI TERHADAP PENJALARAN DAN RUN-UP TSUNAMI 1 DIMENSI STUDI KASUS PERAIRAN BARAT SUMATERA DAN SELATAN JAWA - R. SITORUS , ESTER
This final project simulates the tsunami propagation 1D applied in the 20 location that locate on the west Sumatera and south coast Java to observe the bathymetry respond due to tsunami propagation and run-up. Scale model was used to model the tsunami propagation that has been developed by Imamura and been modified by Hamzah Latief so it can be used to simulate the wave propagation in 1 D. The input data for this simulation is initial wave in the certain time series. The tsunami propagation is effected by bathymetry profile. The simulation has been done in the 20 location that lay down along west Sumatera coast and Java coast result the wave height which not have any difference in Sumatera nor in Java. Results from 2 hours simulation, wave height on Sumatera coast about 6-8 m inundate the coast area about ±2 km but in Java coast just inundate about ±500 m. From this result we can see that run-up height and inundation area is influenced by the topography. This final project's result supposed can give beneficial especially to predict the wave height due to the characteristic certain bathymetry profile.